On the Construction of d-Koszul algebras - Jawad, Ruaa Yousuf (Iraqi Journal of Science, 2020)
An algebra has been constructed from a (D, A)-stacked algebra A, under the conditions that , A 1 and . It is shown that when the construction of algebra B is built from a (D, A)-stacked monomial algebra A then B is a d-Koszul monomial algebra.